Limited relationships between mangrove forest structure and hydro-edaphic conditions in subtropical Queensland, Australia. (5th January 2021) - Hill, Jack W.; Bourke, Lachlan A.; Horton, Ciara M.; Staples, Timothy L.; Lovelock, Catherine E.
Abstract: Mangroves are important ecosystems of the global subtropical zone providing a wide range of ecosystem services. They are sensitive to human disturbances and climate change. However, regional assessments of species composition, forest structure and soil characteristics, and knowledge of the environmental factors that contribute to regional variation in their characteristics are limited. We surveyed mangrove communities at seven island locations along 450 km of the sandy south-east Queensland coast. We found no latitudinal trends in richness of common species or their abundance, likely due to shared climatic conditions across our study range, however there was considerable variation in forest structure among and within the seven sites. Over all sites, analysis of soil characteristics identified four hydro-edaphic environmental categories differing in soil water content, dry bulk density, organic matter and porewater salinity, which also varied spatially among and within sites. There were few strong relationships among forest structure and hydro-edaphic categories, although relatively small trees and high stem densities tended to be associated with soils having high soil water content, high levels of soil organic matter and low bulk density, while forests with largest trees and lowest stem densities tended to be associated with soils with intermediate characteristics, indicative of regular inundation and drainage. The two most common species ( Avicennia marina and Rhizophora stylosa ) had very broad distributions over the four hydro-edaphic categories, although A. marina tended to be more strongly associated with soils with high water content where R. stylosa had a lower probability of occurrence. Bruguiera gymnorrhiza had high fidelity to locations with low porewater salinity influenced by groundwater. We conclude that hydrological conditions are key determinants of mangrove soil characteristics, but less important in determining forest structure in the subtropics. Our study provides a baseline from which future change in mangrove soils and forest structure can be detected. Highlights: We surveyed mangroves over 450 km of subtropical sand islands. Forest structure was not strongly linked to soil characteristics. We found no clear latitudinal trends in forest structure or soil characteristics. We established a detailed baseline for future change detection.